2022
DOI: 10.1111/tbed.14536
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome analysis of African swine fever virus isolated from domestic pigs during the first ASF outbreaks in India

Abstract: African swine fever (ASF), considered as the most dreadful swine disease due to its very high mortality, emerged in India in 2020. The complete genome analysis of ASF viruses isolated during the first outbreaks in India showed a few unique nonsynonymous mutations in MGF 369-11L, MGF 505-4R, K205R and B263R genes. Frame shifts in the protein coding sequences were observed in DP60R, ASFV-G_ACD 00190, MGF 110-10-L-MGF110-14L fusion, MGF 360-14L and I267L genes of Indian ASF viruses as compared to ASFV/Georgia/200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Senthilkumar et al were the first to reveal the genomic analysis of the Indian strain, which is distantly linked to the Asian endemic strain. One important characteristic that could help identify the Asian endemic strain is the Mismatch between the I73R and I329L genes ( Senthilkumar et al, 2022 ). ASFV genotyping in Sabah in 2021 revealed that this strain is comparable to the endemic strains in China, Vietnam, and Indonesia ( Khoo et al, 2021 ).…”
Section: Genetic Variability Of Asfvmentioning
confidence: 99%
“…Senthilkumar et al were the first to reveal the genomic analysis of the Indian strain, which is distantly linked to the Asian endemic strain. One important characteristic that could help identify the Asian endemic strain is the Mismatch between the I73R and I329L genes ( Senthilkumar et al, 2022 ). ASFV genotyping in Sabah in 2021 revealed that this strain is comparable to the endemic strains in China, Vietnam, and Indonesia ( Khoo et al, 2021 ).…”
Section: Genetic Variability Of Asfvmentioning
confidence: 99%
“…DP60R [51] , D129L, DP79L, D339L, D1133L [52] , and D117L were non-expressed ORFs in GRG2007. However, all of them had a high expression level in HLJ2018.…”
Section: Discussionmentioning
confidence: 95%
“…ASFV was first identified in Africa in 1921 and spread to the Caucasus region in 2007, spreading through Russia and East Europe, affecting many countries such as Romania, Poland, Latvia, Hungary, and Czech Republic, and more recently reaching Western European countries, including Belgium, Italy, and Germany [2]. Currently, it is endemic in China, the world's largest pork producer, where it was first detected in 2018 [3], and presently affects neighboring countries such as Vietnam, Laos, Myanmar, Korea, the Philippines, Indonesia, and India [4][5][6]. It emerged in 2021 for the first time in many decades in the Americas, namely in the Dominican Republic and Haiti [7].…”
Section: Introductionmentioning
confidence: 99%